PENINGKATAN KOMPETENSI GURU DENGAN PEMANFAATAN ICT MELALUI APLIKASI PROTEUS DI SMK SETIA BUDI BALIKPAPAN - Maria Ulfah; Andi Sri Irtawaty; Hadiyanto .; Ali Abrar; Erick Sorongan (Universitas Muhammadiyah Ponorogo, 2017)
Based on the problems SMK Setia Budi Balikpapan related limitations of the amount of equipment supporting Digital subjects, therefore the team PkM Balikpapan State Polytechnic community service activities with the title